Recommendations for ensuring customs security based on adaptation to the integrated level of customs danger - Bohdanovych , Vladimir; Marko, Ivan; Yakovlieva, Tetiana; Saienko , Serhii (Social Development and Security, 2021)
The article presents recommendations for customs security based on adaptation to the integrated level of customs danger. The current and future security environment is characterized by a wide range of dangers and threats, intensification of the struggle for access to the latest high technologies, resources and markets, which has a destructive effect on economic and customs security of the state. It is proposed to decompose hazards and threats by areas of manifestation, build a three-level model of assessment by the technology of hierarchical analysis and assess the integrated level of customs risk at the selected time. Then the distinctive levels and thresholds of customs danger are determined by expert means, in particular: the level (threshold) of mutually beneficial cooperation; level (threshold) of increased customs danger; level (threshold) of the pre-crisis customs situation; level (threshold) of the crisis customs situation. This allows the customs security system to adapt to the value of the integrated level of customs danger by choosing one or another mode of operation of the system: the mode of mutually beneficial cooperation; high alert mode; pre-crisis customs situation, anti-crisis regime. This increases the validity of management decisions in customs and economic security systems, increases the efficiency of response to dangers and threats of customs and economic nature, provides conditions for more efficient use of human and other resources available in the system, and generally increases the efficiency of customs and economic security states.